A randomized controlled 30 years follow up of three conventional resin composites in Class II restorations. Issue 10 (October 2015) - Pallesen, Ulla; van Dijken, Jan W.V.
Abstract Objective The aim of this 30 year randomized controlled study was to evaluate, by intraindividual comparisons, the durability of three conventional resin composites in Class II restorations. Methods Each of 30 participants, 21 female and 9 male (mean age 30 years, range 20–43), received at least three (one set) as similar as possible Class II restorations of moderate size. After cavity preparation, the three cavities were chosen at random to be restored with two chemical-cured (P10, Miradapt) and one light-cured resin composite (P30). A chemical-cured enamel bonding agent was applied after etching of the enamel. The chemical-cured resin composites were placed in bulk and the light-cured in increments. One operator placed 99 restorations (33 sets). The restorations were evaluated with slightly modified USPHS criteria at baseline, 2, 3, 5, 10, 15, 20 and 30 years. Statistical analyses were performed by the Kaplan–Meier, log-rank test and Cox regression analyses. Results After 30 years, 5 participants with 15 restorations (15%) could not be evaluated during the whole evaluation. Seven participants were considered as caries risk and eight participants as having active parafunctional habits. Postoperative sensitivity was observed in 24 teeth. In total 28 restorations, 9 P10, 12 P30 and 7 Miradapt restorations failed during the 30 years. The main reasons for failure were secondary caries (39.2%) and material fracture (35.7%). Sixty-four percent of the secondary caries lesions were found in high caries risk participants and 70% of the material fractures occurred in participants with active parafunctional habits. The overall success rate at 30 years was 63%, with an annual failure rate of 1.1%. 68–81% of the restorations showed non-acceptable color match. No statistical significant difference in survival rate was found between the three resin composites (p = 0.45). The variables tooth type, cavity size, age, and gender of the participants did not significantly affect the probability of failure. Significance The three conventional resin composites showed good clinical performance during the 30 year evaluation. The chemical cured resin composites showed better performance than the light-cured composite.